The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1093/jn/121.4.498
|View full text |Cite
|
Sign up to set email alerts
|

Ileal Compensation for Age-Dependent Loss of Jejunal Function in Rats

Abstract: Adaptive responses of brush border hydrolases and crypt cell proliferation were measured in the jejunum and ileum of 4-mo-old adult and 28-mo-old senescent male Wistar rats. Responses were measured after rats were deprived of food and then refed with a normoprotein diet (17% protein) or an isoenergetic high protein diet (70% protein). The young rats deprived of food then refed for 18 h with the high protein diet showed better body weight recovery than did old animals. Withholding food for 48 h induced a more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Maintenance of adequate intestinal structure and function depends on the ability of the intestine to adapt to environmental changes. However, these adaptative capacities are altered during ageing [26]. In our study, intestinal morphometry was affected throughout the experimentation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Maintenance of adequate intestinal structure and function depends on the ability of the intestine to adapt to environmental changes. However, these adaptative capacities are altered during ageing [26]. In our study, intestinal morphometry was affected throughout the experimentation.…”
Section: Discussionmentioning
confidence: 72%
“…To the best of our knowledge, the response of the small intestine to changes in dietary composition is poorly understood in aged rats and has primarily been investigated in response to short‐term starvation [26–28]. This latter condition leads to rapid and dramatic changes in the morphology of intestinal mucosa [26, 27]. Accompanying the mucosal atrophy, some alterations of intestinal functions were described in this study, in particular concerning the permeability of the mucosa.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Intestinal microflora extensively degrade gums but only partially degrade cellulose. It is reported that there are some differences in intestinal function between the young adult and aged mice [11] and between the young adult and aged rats [12]. However, there is little information on the cecal enzyme activity and cecal short-chain fatty acids in aged mice fed different dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive capacities of the hydrolases to the changes in the diet composition during refeeding are strikingly deficient in the proximal intestine of aged rats. However, these proximal deficiencies are compensated by enhanced ileal functions (Reville et al 1991).…”
Section: Effects Of Ageingmentioning
confidence: 99%